2020
DOI: 10.1093/nar/gkaa852
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms coordinating ribosomal protein gene transcription in response to stress

Abstract: While expression of ribosomal protein genes (RPGs) in the budding yeast has been extensively studied, a longstanding enigma persists regarding their co-regulation under fluctuating growth conditions. Most RPG promoters display one of two distinct arrangements of a core set of transcription factors (TFs) and are further differentiated by the presence or absence of the HMGB protein Hmo1. However, a third group of promoters appears not to be bound by any of these proteins, raising the question of how the whole su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
58
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 66 publications
7
58
0
Order By: Relevance
“…It was recently reported that overexpression of CRF1 rescues the lethality of an IFH1 deletion, suggesting that it can substitute for Ifh1p as an activator when in excess, and that it prevents rapamycin-mediated repression of Category I and II RP genes, which depend on Fhl1p and Ifh1p for regulation of gene expression (Zencir et al, 2020). Notably, our data indicate that Crf1p functions as an activator under normal growth conditions ( Figures 4F and S4).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…It was recently reported that overexpression of CRF1 rescues the lethality of an IFH1 deletion, suggesting that it can substitute for Ifh1p as an activator when in excess, and that it prevents rapamycin-mediated repression of Category I and II RP genes, which depend on Fhl1p and Ifh1p for regulation of gene expression (Zencir et al, 2020). Notably, our data indicate that Crf1p functions as an activator under normal growth conditions ( Figures 4F and S4).…”
Section: Discussionsupporting
confidence: 64%
“…Surprisingly, deletion of CRF1 resulted in >2-fold lower levels of HMO1, UTP22, and RRP7 mRNA. By comparison, expression of RP genes was not markedly altered in tor1D cells but expression of Class I and II RP genes, which have been reported to depend primarily on Fhl1p and its cofactors for regulation (Fermi et al, 2016;Knight et al, 2014;Zencir et al, 2020), was reduced on deletion of CRF1 ( Figure S2F). The reduction in mRNA levels in crf1D cells suggests that Crf1p functions as an activator.…”
Section: Crf1p Functions As An Activatormentioning
confidence: 90%
“…A general pattern of this combined response is the “normalization” of the level of expression of many genes that have been downregulated (including many ribosomal proteins) or upregulated (including oxidoreductases and several metabolic enzymes like glyceraldehyde-3-phosphate dehydrogenase and malate dehydrogenase) by OS. Downregulation of ribosomal proteins expression is a conserved mechanism to shut down unnecessary protein synthesis during stress [ 44 ]. In contrast, the upregulation of oxidoreductases and metabolic enzymes expression is a mechanism that compensate the inhibition of activity of these essential enzymes for the parasite following their oxidation [ 35 ].…”
Section: Response Of E Histolytica To Os In Prmentioning
confidence: 99%
“…Ribosomal protein (RP) genes are frequently analyzed as a separate gene category due to high expression levels, common regulatory mechanisms, and important roles in cell growth and stress response ( Zencir et al, 2020 ). About 95% of RP genes belong to the TFIID-dependent class ( Donczew et al, 2020 ; Huisinga and Pugh, 2004 ).…”
Section: Resultsmentioning
confidence: 99%